Atuação do professor supervisor em um grupo PIBID/Química: Performance of the supervising professor in a PIBID/Chemistry group (Revista Cocar, 2021)
Neste artigo são apresentados os resultados da análise de uma entrevista realizada com um professor supervisor (PS) participante do PIBID de um curso de Licenciatura em Química. O foco deste trabalho pautou-se na atuação do PS, priorizando as percepções e interações desse professor com atores no momento de sua atuação no Programa. A análise e interpretação dos dados seguiu os pressupostos da Análise de Conteúdo. Como resultados, destaca-se que a participação do professor supervisor no PIBID resultou em contribuições para a sua formação docente mediada pela proposta de elaboração das Trajetórias Hipotéticas de Aprendizagem como instrumento/abordagem de ensino para as aulas de Química. Além disso, as interações estabelecidas pelo PS com os atores envolvidos no Programa demonstraram o estreitamento entre a escola/universidade e revelam indícios de ressignificação de sua prática docente.Palavras-chave: Trajetórias hipotéticas de aprendizagem; PIBID; Ensino de Química. Abstract This article presents the results of the analysis of an interview conducted with a supervising professor (PS) participating in the PIBID of a Chemistry Degree course. The focus of this work was based on the performance of the PS, prioritizing the perceptions and interactions of this teacher with actors at the time of his performance in the Program. The analysis and interpretation of the data followed the assumptions of the Content Analysis. As a result, it is emphasized that the participation of the supervising professor in PIBID resulted in contributions to his teacher training mediated by the proposal to elaborate Hypothetical Learning Trajectories as a teaching instrument / approach for Chemistry classes. In addition, the interactions established by PS with actors involved in the Program demonstrated the narrowing between the school/university and reveal signs of redefinition of their teaching practice.Keywords: Hypothetical learning trajectories; PIBID; Chemistry Education.